PEMEROLEHAN BAHASA PADA ANAK USIA 2 TAHUN 101 HARI PADA KELAS KATA VERBA - Maurine Irena (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
Language is the main means of communication in human life in this world, both in oral, written, or only in the form of certain symbols. As social human beings cannot communicate without language, humans inevitably have to interact with other humans. This research is a case study related to the acquisition of children's language in verb word classes in early childhood. Related to that, mastery of a language can be learned formally through understanding how the language is formed and created. Extensive knowledge about the process and nature of language acquisition can greatly help children in the success of language learning in children. To determine the division of children's language acquisition stages based on the average length of speech (PRU) or mean length of utterance (MLU)